2008
DOI: 10.1128/jcm.00787-07
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Screening for Acute Human Immunodeficiency Virus Infection with Pooled Nucleic Acid Amplification Tests

Abstract: Recent studies have shown the public health importance of identifying individuals with acute human immunodeficiency virus infection (AHI); however, the cost of nucleic acid amplification testing (NAAT) makes individual testing of at-risk individuals prohibitively expensive in many settings. Pooled NAAT (or group testing) can improve efficiency and test performance of testing for AHI, but optimizing the pooling algorithm can be difficult. We developed simple, flexible biostatistical models of specimen pooling w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 35 publications
0
114
0
5
Order By: Relevance
“…enrichment by hard spinning) and the incidence of HIV in the targeted population are quite critical to the success and cost effectiveness of MP-NAAT. Low viral load sero-conversion panels are prone to viral RNA dilution of the mini-pools, below the detection threshold of the NAAT, though various studies have confirmed its reliability [4][5][6]8,9,17,21,26,27,32,34,35]. An average clinical sensitivity of 98% was recorded for pooled NAAT using IDT NAAT as v from the studies included in this review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…enrichment by hard spinning) and the incidence of HIV in the targeted population are quite critical to the success and cost effectiveness of MP-NAAT. Low viral load sero-conversion panels are prone to viral RNA dilution of the mini-pools, below the detection threshold of the NAAT, though various studies have confirmed its reliability [4][5][6]8,9,17,21,26,27,32,34,35]. An average clinical sensitivity of 98% was recorded for pooled NAAT using IDT NAAT as v from the studies included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, of those anti-HIV repeat reactive samples that tested NAAT nonreactive and Western blot negative or indeterminate, 98.5% had an Abbott ELISA signal-cutoff ratio less than 15 [15]. The need for an optimized and realistic algorithm and pool size that is cost effective, for different settings and incidences via-as-vis methodology (such as hard spinning), taking into account HIV 1 genetic diversity, primerprobe mismatch and platforms as summarized in Table 6 below, cannot be over emphasized [16][17][18][19][20][21][22][23]26,27,[36][37][38][39][40][41][42][43][44][45]. Cannillo et al recently, reported that CAD as the most frequent cardiac complication in HIV patients (particularly those with low CD4 and high viral load) treated with HAART.…”
Section: Need For Population Specific Screening Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these situations, confirmation of an HIV diagnosis can be made from venous blood samples sent to a virology laboratory where the presence of viral proteins (p24) or viral HIV DNA or RNA can be made. 13 Laboratory third generation tests do not detect viral gag protein (p24) and therefore are less able to detect early infection prior to the development of detectable levels of HIV antibody. The lack of detectable antibodies in the initial stages of infection makes this a difficult diagnosis to make using current standard tests.…”
Section: Challenges Of Phi Diagnosismentioning
confidence: 99%
“…The diagnostic challenge posed by AHI has inspired screening efforts involving complex and expensive laboratory procedures using pooled nucleic acid amplification test (pNAAT) algorithms. 5,15,16 Programs designed to increase the ascertainment of AHI by pNAAT have been conducted and described in North Carolina, 5,17 Seattle (Washington), 18 Los Angeles (California), 19 San Francisco (California), 20 and New York City (NYC). 21 While effective in increasing the detection of AHI, such pNAAT programs are costly, and targeting their use to the highest-yield populations to maximize efficiency has been recommended.…”
mentioning
confidence: 99%